Additions to the knowledge of Trichogramma from Turkey (Hymenoptera: Trichogrammatidae), with description of a new species. Issue 4 (2nd October 2022) - Polaszek, Andrew; Rugman-Jones, Paul; Çelik, Hakan; Bolu, Halil
Abstract : New country and host records of Trichogramma species for Turkey are presented. Trichogramma aurosum Sugonjaev & Sorokina is recorded for the first time from Turkey, and a new species, T. zerynthiae Polaszek & Bolu, is described. Morphological identification based on dissected male genitalia is supplemented by molecular sequence data. http://www.zoobank.org/urn:lsid:zoobank.org:pub:9CFF5E39-F1D2-42FB-86B8FC8475EC3560